Economic implications of intensive early stocking on feeder cattle markets and land values in the Flint Hills - Brence, Meghan K. (Kansas State University, 2021)
Over the past 45 years, intensive early stocking (IES) has become the preferred grazing system of cattle producers in the Flint Hills region. Intensive early stocked steers gain more per day compared to their season-long (SLS) counterparts since they are stocked at twice the normal stocking density until mid-growing season (Smith and Owensby 1978). They reported that, compared the normal season-long grazing, overall daily gains and gains per acre were increased under IES. Because of that change, we speculated that there could be a direct effect on feeder cattle prices and land values. More specifically, under IES, steers at marketing time reached more desirable weights than those produced in the SLS system. Therefore, high-quality grazing land should become more desirable than before and feeder cattle prices and land values should increase. That question has not been addressed in the literature to date. This study estimates if, and to what magnitude, the impacts IES in the Flint Hills had on feeder cattle markets and land values in the form of feeder cattle prices and county-level land values. Results show on average an increase in feeder cattle prices of $0.27/cwt per 1% increase in adoption. The Flint Hills has land values that are statistically different than two of four regions of Kansas. In those two regions, IES increased the value of land. Additionally, a survey was conducted to determine whether a producer would opt to change from their current grazing practice to IES, or IES with late season grazing (IES+LSG). Producers surveyed preferred both IES and IES+LSG systems to neither system and with constraints of average daily gain and labor costs, only average daily gain was statistically significant in their decision.
Keywords: Flint Hills; Feeder cattle; Grazing; Intensive early stocking; Late season grazing; Stocker cattle